Updated assessment of ground-dwelling mammals in Ayer Hitam forest reserve, Selangor - Baharudin, Nur Syakirah; Mohd. Top @ Mohd. Tah, Marina; Rabbani Subari @ Subiyri, Mohd Faris; Mazlan, Nur Sa'adah; Tengku Azizan, Tengku Rinalfi Putra (Universiti Malaysia Terengganu, 2022)
This study focus on Compartment 14 of the Ayer Hitam Forest Reserve (AHFR) aims to fill-in the 16-year research gap in the compartment under review and provide up-to date survey data on the various species and composition of said species especially nonvolant small mammals for future reference, conservation, and management. The survey of species diversity and composition of mammals in AHFR was carried out over a five-month period from November 2017 to March 2018. The methods used to collect the data used in this study include live trapping and camera trapping used simultaneously. These methods were used to specifically quantify and identify mammal species in the study area. This survey identified and recorded nine different species of non-volant small mammals and five species of ground-dwelling big mammals. Live traps that were specifically designed to capture non-volant small mammals managed to record five of the species. Camera traps used in the survey captured data on both small non-volant mammals and grounddwelling big mammals recorded seven non-volant small mammal species and five species of big ground-dwelling mammal in the study area. The results showed the presence of eight families of mammals consisting of Cercopithecidae, Hystricidae, Muridae, Sciuridae, Suidae, Tragulidae, Tupaiidae and Viverridae. In general, both methods whether camera trapping or live trapping were significantly different from each other in terms of the data collected on species diversity of non-volant small mammals and the camera trap had the highest values on Shannon-Weiner Diversity Index, at H = 1.769 which was slightly more than the values seen using the live trap method, which scored H = 1.365. The data collected on the species composition of non-volant small mammals in the Compartment 14 study area was low which might be due to the excessive amount of human activity such as jogging, hiking and camping in the area. The anthropogenic activity had adversely affected, disturbed and upset the ecological behaviour of ground dwelling mammals in the area. This may have led to a migration of the species to quieter area within AHFR which in turn decreased the biodiversity within Compartment 14.